Balancing sub-unit autonomy and collective problem-solving by varying exit and voice. An analytical framework. Issue 4 (11th April 2017) - Jachtenfuchs, Markus; Kasack, Christiane
ABSTRACT: We argue that there is a commonality between federal states and the EU: both face a dilemma between sub-unit autonomy and collective problem-solving. We develop the structure of this dilemma, which is pervasive in multilevel systems with a strong element of shared policy-making and most pronounced in the EU. While a substantial part of the federalism literature considers this relationship as precarious and discusses ways to stabilize it, we propose an analytical perspective which focuses on actor dynamics, i.e., on the attempts of sub-units to change the balance between sub-unit autonomy and collective problem-solving by changing their position in two distinct dimensions: exit and voice . Exit measures the degree to which sub-units want to be subject to collective policies, voice measures the influence sub-units seek in collective decisions. We illustrate this framework with examples, mainly from the EU, and conclude that this perspective can shed new light on differentiated integration in the EU and open comparative inquiries.